Scene of the crime : tracking down criminals with forensic science - Newquist, H. P. (Harvey P.) (Viking Books, 2021)
"Critically acclaimed author, HP Newquist, writes about the history of forensic science for young readers. The book also includes classroom activities and full-color photos "--